Strategic innovation and sustainability : rethinking management for the future of business - Szozda, Natalia; Bugaj, Justyna M. (Routledge, 2026)
Drawing together research from across Central and Eastern Europe, this volume examines how organisations navigate the complex intersection of strategic innovation, digital transformation, and sustainability in emerging economies.Through 14 empirically-grounded chapters, the book reveals how companies across finance, healthcare, tourism, e-commerce, and manufacturing sectors respond to uncertainty while pursuing responsible business practices. The book offers unique value through its dual focus on academic rigour and practical application. Each chapter provides methodologically diverse insights - including case studies, surveys, and mixed-methods research - alongside concrete managerial recommendations. The three-part structure explores strategic paradoxes, digital technology implementation, and ESG integration, presenting a comprehensive framework for building resilient organisations in transitional economies.This edited volume serves multiple audiences: Researchers, academics, and PhD students will find current research directions and methodological approaches; business leaders and policymakers will gain frameworks for implementing effective innovation strategies; and advanced students across business, sustainability, and regional studies programmes will benefit from its balanced theoretical and practical perspectives.
Keywords: Organizational change.; Social responsibility of business.; Technological innovations.; elektronické knihy; electronic books